Modelo para la distribución de medicamentos a comunidades en zonas apartadas de la región costera del departamento del Chocó, Colombia (2021)
Health supply chains present many problems in the processes of supplying, storing and distributing inputs and medicines, due to uncertainty in demand, diagnostics and short product life cycles. In rural and remote areas, this complexity increases due to accessibility restrictions, modes of transport, population dispersion and long distances. Proper management of these chains is essential to preserve the health of the population. For this reason, the state, as the regulatory body of the health system, should design strategies that fit the context of these regions and ensure maximum coverage of health services. In Colombia, this situation is mainly reflected in public health programs for poor and vulnerable territories, limiting the availability of medicines in a timely manner to the population, generating high rates of morbidity and mortality. This research sets out a model for the distribution of medicines of public health interest to remote areas, where there are geographical barriers, it chooses access infrastructure, rurality and dispersion. It is proposed for transport, use air mode by means of UAV vehicles and its possibility of integration with river mode, which is currently the most exploited in the area for the transport of cargo and passengers. The study is carried out using mixed techniques, combining qualitative approaches to the characterization of the current distribution operation in the region, and quantitative for the design of a distribution model using exact mathematical formulation techniques. The results show that making use of intermodal transport with UAV vehicles and boats, distribution time is reduced by 25% and drug availability for the population is improved. This work is carried out within the framework of the project “Technologies in demand management and logistics operation in a health care network in the coastal region of the Department of Chocó. An approach from the beneficiary towards the institutionalism”.